Solar Power-Based Thermo Electric Cooler (TEC) System - Situmorang, Marhaposan; Panjaitan, Monika (Talenta Publisher, 2021)
Solar energy has been considered as a promising renewable energy source for electric power generation. Solar panel systems have become a popular object to be developed by researchers, but the low efficiency of solar panels in energy conversion is one of the weaknesses of this system. Factors that affect the output produced by solar panels are the intensity of sunlight and the working temperature of the solar panels. The solar panel module has a single operating point where the voltage and current outputs produce the maximum power output. There are three main methods in Maximum Power Point Tracking (MPPT), namely conventional methods, artificial intelligence methods, and hybrid methods. In most solar panel systems, this study uses Maximum Power Point Tracking (MPPT) with perturb and observe algorithms to maximize the use of solar energy. The maximum power point extracted by MPPT will be supplied to the battery and controlled by the Charge Controller. The energy stored in the battery will be used by the Thermo Electric Cooler cooling system to reach the desired temperature point using the keypad as temperature input.